Technologies and children up to 8 years old: what changes in one year? - Brito,Rita (2019)
In this chapter, we present a longitudinal study which aims to explore the involvement of children up to 8 years old and their families with digital technologies, focusing perceptions and use, during a one-year period. In a first phase, ten families with children up to 8 years old were interviewed. In a second phase, we interviewed eight of the initial ten families. In both moments, children elected the tablet as their favourite device, and their preferred activities were playing games and watching videos on YouTube. Due to an increase in their reading and writing skills, on the second visit to families, we observed that children had become more autonomous in their digital practices, being able to search about their interests and refine such searches. In addition, parents showed more positive perceptions regarding the use of technologies by their kids, promoting their use for scholar searches. The type of parental mediation is related to the parents' perceptions about technologies: parents who consider their use beneficial for more pedagogic purposes, encourage their children, monitoring and supporting them, thus leading to their children using and perceiving the Web as an important tool to explore personal and school interests; parents who hold a less positive view about digital media do not encourage their use, not even for pedagogic purposes, frequently restricting screen-time, and therefore their children use the devices for limited time and mostly for play activities.